Pendidikan Kesehatan Pengecahan Penularan COVID-19 Melalui Penyuluhan Rumah Sehat Dan Mencuci Tangan - Sandy Kurniajati; Aries Wahyuningsih (Pelita Abdi Masyarakat, 2022)
Background: The Covid-19 pandemic that occurred in early 2020 is a major health problem today. Unhygienic human behavior and high human mobilization are one of the factors that spread the Covid 19 health problem that is difficult to control. Through Psychological Distancing, it is hoped that everyone will stay at home, so the family is the most important unit in the success of preventing the transmission of this health problem. Method: Families can become subjects in increasing their ability to provide a healthy home environment and behavior that supports family members' hygiene and sanitation so that they can encourage families to have optimal health. and supports handwashing behavior in preventing the spread of Covid 19 health problems. Result: The results of the implementation of health education activities All families (100%) received counseling on healthy homes, how to wash hands, and available handwashing and soap facilities in the community. Conclusion: The conclusion of implementing community service was that – community/family health education has the awareness to provide a healthy home (available handwashing areas with soap) and increased handwashing behavior after activities inside and outside the home.